Quantitation of pyrazines in Baijiu and during production process by a rapid and sensitive direct injection UPLC-MS/MS approach. (June 2020) - Yan, Yan; Chen, Shuang; He, Yingxia; Nie, Yao; Xu, Yan
Abstract: Pyrazines are one type of the most important aroma compounds in Baijiu, and a novel method of pyrazines detection was developed in this work. Baijiu samples were analyzed by direct injection ultra–performance liquid chromatography coupled with tandem mass spectrometry operating in positive electrospray ionization mode. The approach achieved good extraction recoveries (78.24–102.58%), good repeatability with intra-day, inter-day, and inter-week relative standard deviations of 0.84–4.17%, 0.78–6.71%, and 4.50–8.61% in respective, and short analysis time. Moreover, the optimized method was applied to the analysis of different typical aroma-type Baijiu. The unsupervised principal component analysis clearly differentiated four typical aroma-type Baijiu samples based on the pyrazines concentrations. The pyrazines concentrations showed a significant increase during fermentation steps and distillation time. This work provides an efficient strategy for determining the pyrazines levels in Baijiu and is beneficial for improving Baijiu quality. Highlights: A new quantitative UPLC-MS/MS method for analysis of pyrazines has been developed. The types of Baijiu showed high correlations with pyrazines concentrations. A general trend of increasing pyrazines concentrations for the Baijiu production process. Soy sauce aroma-type Baijiu have significantly higher pyrazines concentrations than other aroma-type Baijiu.